Cultivating green workforce: The roles of green shared vision and green organizational identity - Ma, Xuejun; Bashir, Hasnain; Ayub, Arslan (Frontiers in Psychology, 2023)
Introduction The current study anchors on the social identity theory (SIT) and social exchange theory (SET) to investigate the association between green talent management (GTM) and employee retention (ER), mediated by green organizational identity (GOI). Further, the study projects the moderator effect of green shared vision (GSV) in the direct association between GTM and GOI, and the indirect link between GTM and ER through the mediator effect of GOI. Methods We collected time-lagged (i.e., three-wave) data from 495 frontline managers in the tourism service firms in Pakistan. Data are analyzed using SmartPLS SEM (V 3.3) to evaluate the measurement and structural models. Results Our results support all the projected associations and confirm the direct relationships between GTM and ER (β = 0.480, CIs = 0.494, 0.578), GTM and GOI (β = 0.586, CIs = 0.517, 0.670), and GOI and ER (β = 0.492, CIs = 0.425, 0.566). The findings further reveal that GOI significantly mediates the relationship between GTM and ER (β = 0.257, CIs = 0.184, 0.312). In addition, the moderator effect of GSV significantly underpins the direct association between GTM and GOI (β = 0.512, CIs = 0.432, 0.587) and the indirect association between GTM and ER, mediated by GOI (β = 0.526, CIs = 0.441, 0.590). Discussion This is the first study that explores a moderated mediation model to explain when and how tourism service firms can promote ER through inculcating GTM strategies. The findings indicate that service firms in the tourism industry must develop and retain green talent to exploit pro-environmental strategies.